Biochar Application Mitigates the Effect of Heat Stress on Rice (Oryza sativa L.) by Regulating the Root-Zone Environment - Huang, Min; Yin, Xiaohong; Chen, Jiana; Cao, Fangbo (Frontiers in Plant Science, 2021)
Coping with global warming by developing effective agricultural strategies is critical to global rice production and food security. In 2020, we observed that the effect of heat stress on rice plants was mitigated by biochar application in a pot experiment. To further determine the eco-physiological processes underlying the effect of biochar on resistance to heat stress in rice plants, we compared root-zone soil properties as well as some plant growth and physiological traits related to nitrogen (N) utilization between rice plants grown with and without biochar in the pot experiment. The results showed that the application of biochar improved the root-zone environment of rice plants by reducing soil bulk density, increasing soil organic matter content, and altering soil bacterial community structure by increasing the ratio of Proteobacteria to Acidobacteria, for example. As a consequence, root morphology, architecture, and physiological traits such as the expression of N assimilation and transport proteins, as well as shoot N uptake and utilization (e.g., the expression of photosystems I and II proteins) were improved, while the expression of heat-shock and related proteins in roots and leaves were down-regulated in rice plants grown with biochar compared to those without biochar. These results not only expand our understanding of the basic eco-physiological mechanisms controlling increased heat-stress tolerance in rice plants by the application of biochar, but also imply that improving the root-zone environment by optimizing management practices is an effective strategy to mitigate heat stress effects on rice production.